Koreografi Tari Toga pada Sanggar Dara Petak Kerajaan Siguntur di Kabupaten Dharmasraya - Hartanti, Rezil; Nerosti, Nerosti (Lembaga Yasin AlSys, 2025)
This study is motivated by the importance of choreographic documentation and analysis in the preservation of traditional performing arts, specifically Tari Toga, a dance originating from Sanggar Dara Petak of the Siguntur Kingdom in Dharmasraya Regency. The research aims to provide a comprehensive description of the choreographic elements of Tari Toga, which reflect the historical and philosophical identity of the local community. A qualitative approach with a descriptive-analytical method was employed. The primary research instrument was the researcher, supported by writing tools, a camera, and a flash drive. Data collection techniques included literature review, observation, interviews, and documentation. Data analysis was conducted through the stages of collection, reduction, presentation, and conclusion drawing. The findings reveal that the choreography of Tari Toga comprises elements of movement (space, time, energy), floor patterns, musical accompaniment, props, makeup, and costumes. Spatial design incorporates symmetry, asymmetry, and vertical patterns; temporal design manages long and short durations according to movement character; and energy design emphasizes identity and expressive force. Floor patterns include curves, straight lines, and diagonals, each carrying symbolic meaning. The accompanying music features gong, kenong, momong, gendang, and talempong. Makeup employs a classic beauty style, while costumes consist of baju kurung, headdresses, jewelry, and songket fabric. The study concludes that the choreography of Tari Toga embodies a fusion of aesthetic beauty and cultural values, playing a vital role in preserving local cultural heritage.